LAS SUBORDINADAS CAUSALES EN LAS CARTAS DE PLINIO - Guzmán Arias, Carmen (Myrtia, 1990)
In this paper the causal propositions are analyzed as they are used in Pliny the Younger ’Letters’, where phrasal propositions express the reason or the causal motive of the action enunciated in the principal clause. The conjunctions of principal frequency are established, the aim being to ascertain whether the use is a regular or diversified one. In this way, an atempt is made to verify the tendencies of the classic 1st c. prose concerning the expression of subordinate causality.